Patients' Responses to COVID-19 Pandemic: The Relationship Between Potential Pandemic-Induced Disruptions, Ontological Security, and Adaptive Responses in Taizhou, China - Luo, Chengwen; Wu, Xiaoyan; Wang, Weizhen; Zhang, Mei-Xian; Cheng, Fengmin; Chen, Haixiao; Tung, Tao-Hsin (Frontiers in Public Health, 2022)
Background The COVID-19 pandemic has changed the social environment of most individuals around the world and has profoundly impacted people's lives, ontological security, and behavior. Among them, the patients are one of the groups most influenced by the pandemic. Objective The present research aimed to study the relationship of COVID-19 pandemic-induced disruption to patients' daily lives, ontological security, and patients' responses to prevent the spread of COVID-19, and explore the role of ontological security. Methods This article was based on an online structured questionnaire study conducted among hospitalized patients in Taizhou Hospital of Zhejiang Province, Taizhou, China, from 8 July to 11 August 2021. We analyzed the data using the multivariate regression model and mediation analysis method. Results The results showed that the higher the pandemic-induced disruption to inpatients' lives, the better behavior would be taken by hospitalized patients to prevent the spread of COVID-19, and the perceived scarcity of ontological security played a mediating role in this process. Higher pandemic-induced disruption to patients' lives increased the ontological insecurity which further, in turn, reduced patients' good practice toward measures to prevent the novel coronavirus. Conclusion These findings provided direct evidence for the relationship between pandemic-induced disruption, scarcity of ontological security, and patients' prevention behavior. It suggested that there was a need to emphasize patients' ontological security. Overall, these findings suggested that it is important to emphasize the mental health among patients during the COVID-19 pandemic, and implement strategies to offer psychological support when needed.